Addressing the Subjugation of Knowledge in Educational Settings through Structuration of Teacher Research - Edwards, Will; Kalan, Amir (The Canadian Journal of Action Research, 2023)
Building on critical sociological models and action research traditions, our work theorizes a structurated model of action research to address the subjugation of knowledge within educational settings. We focus on the interplay between structure and agency and how these dimensions can co-evolve in teacher research. In this article, we examine how teachers and researchers engaged in collaborative inquiry communities inhabit a complicated role within educational structures. The authors outline and detail rich cases that illustrate the dense particulars of knowledge subjugation within educational structures—these range from the denigration of immigrant students’ credentials to the suppression of indigenous languages. The testimonies of practitioners and students are presented to underscore the inchoate and contradictory conditions that inform educational systems and the meaningful alternative practices that might contravene inequitable structures. The possibilities for recognizing the corrosive mechanisms of knowledge subjugation potentiate resistant parallel structures that invite meaningful inquiry-based methods.